Application of Tepid Sponge Therapy to Treat Hyperthermia in Gestational Age Children at General Hospital : A Pre-Experimental Study - Indra Frana Jaya KK; Citra Suraya; Patimah Patimah; Penti Meka Pratiwi; Indri Kurniasari; Pitri Hasana; Putri Puji Asrini; Raden Ayu Dhiyaa Adelia (School of Health Sciences Al-Ma'arif, 2025)
Fever in infants and children is the most common complaint. Fever is a form of defense from the body in dealing with problems in the body. Fever is not a problem, but a high fever can be serious in all children. This study aims to determine the application of Tepid Sponge therapy to treat hyperthermia in preschool-aged children at Siti Fatimah Regional Hospital, South Sumatra Province. This research used a pra-experimental approach with a one group pre-post test design, the number of respondents was 20 patients diagnosed with hyperthermia, then given Tepid Sponge therapy. Sampling used purposive sampling, data was collected by checking the patient's body temperature values in the pre-test and post-test. The results of statistical tests using the paired t-test showed that there was a decrease in temperature in patients before and after Tepid Sponge therapy with a value of p=0.000. The conclusion of this study is that the application of Tepid Sponge can significantly reduce temperature in pediatric patients who experience hyperthermia. Nurses can include the Tepid Sponge intervention as a complementary nursing therapy and it is hoped that future research can compare its effectiveness with other interventions, use a control group or use a larger sample.